IκB kinase promotes Nrf2 ubiquitination and degradation by phosphorylating cylindromatosis, aggravating oxidative stress injury in obesity-related nephropathy - Yin-Yin Chen; Han Hong; Yu-Ting Lei; Jia Zou; Yi-Ya Yang; Li-Yu He (BMC, 2021)
Abstract Background Obesity-related nephropathy (ORN) has become one of the leading causes of end-stage renal disease and has tripled over the past decade. Previous studies have demonstrated that decreased reactive oxygen species production may contribute to improving ORN by ameliorating oxidative stress injury. Here, IκB kinase (IKK) was hypothesized to inactivate the deubiquitination activity of cylindromatosis (CYLD) by activating the phosphorylation of CYLD, thus promoting the ubiquitination of NF-E2-related factor 2 (Nrf2) and further aggravating oxidative stress injury of the kidney in ORN. This study was aimed to confirm this hypothesis. Methods Haematoxylin and eosin (HE), periodic acid-Schiff (PAS) and Oil Red O staining were performed to assess histopathology. Dihydroethidium (DHE) staining and MDA, SOD, CAT, and GSH-PX assessments were performed to measure reactive oxygen species (ROS) production. Immunohistochemical (IHC) staining, qRT-PCR and/or western blotting were performed to assess the expression of related genes. JC-1 assays were used to measure the mitochondrial membrane potential (ΔΨm) of treated HK-2 cells. Co-immunoprecipitation experiments (Co-IP) were used to analyse the interaction between CYLD and Nrf2 in ORN. Results ORN in vivo and in vitro models were successfully constructed, and oxidative stress injury was detected in the model tissues and cells. Compared with the control groups, the phosphorylation level of CYLD increased while Nrf2 levels decreased in ORN model cells. An IKK inhibitor reduced lipid deposition, ROS production, CYLD phosphorylation levels and ΔΨm in vitro, which were reversed by knockdown of CYLD. Nrf2 directly bound to CYLD and was ubiquitinated in ORN cells. The proteasome inhibitor MG132 activated the Nrf2/ARE signalling pathway, thereby reversing the promoting effect of CYLD knockdown on oxidative stress. Conclusion IKK inactivates the deubiquitination activity of CYLD by activating the phosphorylation of CYLD, thus promoting the ubiquitination of Nrf2 and further aggravating oxidative stress injury of the kidney in ORN. This observation provided a feasible basis for the treatment of kidney damage caused by ORN.